2020
DOI: 10.1371/journal.pone.0234218
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression in equine malignant melanoma and functional effects of PD-L1 blockade

Abstract: Programmed death-1 (PD-1) is an immunoinhibitory receptor expressed on lymphocytes. Interaction of PD-1 with its ligand PD-ligand 1 (PD-L1) delivers inhibitory signals and impairs proliferation, cytokine production, and cytotoxicity of T cells. In our previous studies, we have developed anti-bovine PD-L1 monoclonal antibodies (mAbs) and reported that the PD-1/PD-L1 pathway was closely associated with T-cell exhaustion and disease progression in bovine chronic infections and canine tumors. Furthermore, we found… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The WB analysis (Figure 1) indicated that the anti-human PD-L1 and anti-CTLA-4 antibodies tested cross-reacted with the corresponding equine proteins. A single band corresponding to approximately the expected molecular weight of the equine PD-L1 (42.4−50.3 kDa) [35] was detected in the placenta, whereas no positive signal was observed in the liver lane. A single band of approximately 25 kDa corresponding to the expected molecular weight of CTLA-4 (https://www.uniprot.org/uniprot/F6WWE3, accessed on 23 April 2021) was detected in the lymph node but was negative in the placenta lane.…”
Section: Western Blottingmentioning
confidence: 90%
“…The WB analysis (Figure 1) indicated that the anti-human PD-L1 and anti-CTLA-4 antibodies tested cross-reacted with the corresponding equine proteins. A single band corresponding to approximately the expected molecular weight of the equine PD-L1 (42.4−50.3 kDa) [35] was detected in the placenta, whereas no positive signal was observed in the liver lane. A single band of approximately 25 kDa corresponding to the expected molecular weight of CTLA-4 (https://www.uniprot.org/uniprot/F6WWE3, accessed on 23 April 2021) was detected in the lymph node but was negative in the placenta lane.…”
Section: Western Blottingmentioning
confidence: 90%
“…EV-associated PD-L1 plasma levels also increased with tumour burden in a murine model and in humans, and was higher in metastatic versus non-metastatic melanoma cell lines [ 78 ]. PD-L1 therapies may be applied to canine [ 89 , 90 ] and equine melanoma [ 91 ] patients, and by extension to other species.…”
Section: Role Of Evs In Monitoring Melanoma Progressionmentioning
confidence: 99%
“…The complementary DNA (cDNA) was synthesized from mRNA of swine PBMCs stimulated with 20 ng/ml phorbol 12‐myristate acetate (PMA; Sigma‐Aldrich) and 1 μg/ml ionomycin (Sigma‐Aldrich) for 24 h. The cultivation of PBMCs, total RNA isolation, and cDNA synthesis was conducted as described previously 16 . The cDNAs encoding swine PD‐1 and PD‐L1 were amplified by PCR using TaKaRa Ex Taq (Takara Bio) and gene‐specific primers with restriction enzyme cleavage sites (Table ), and then subcloned into pEGFP‐N2 (Clontech).…”
Section: Methodsmentioning
confidence: 99%
“…The protein concentration was measured by ultraviolet absorbance at 280 nm with a NanoDrop 8000 Spectrophotometer (Thermo Fisher Scientific). The binding of rPD‐1 and rPD‐L1 to COS‐7 cells expressing swine PD‐L1‐EGFP and PD‐1‐EGFP was investigated using flow cytometry as described previously 16 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation